Islanding detection in distributed generation system based on optimized KNN utilizing S-transform based features - Mishra, Manohar; Patra, Chinmoy Kumar; Muni, Pratyush Kumar; Gadanayak, Debadatta Amaresh; Parida, Tanmoy (2023 International Conference in Advances in Power, Signal, and Information Technology (APSIT), 2023)
This paper presents an islanding detection approach for integrated distribution systems that incorporate distributed energy resources (DERs). The approach utilizes the S-transform and an ensemble K-Nearest Neighbor model (KNN). Initially, the S-transform is employed to extract the characteristic features of the system signals, effectively capturing the transient power variations that occur during islanding events. Subsequently, a KNN model is developed to classify the system states as either islanding or non-islanding. To achieve high accuracy and generalization performance, the KNN model is optimized using a Bayesian optimization algorithm. The proposed approach is evaluated on a simulated DER-integrated distribution system, considering various scenarios, and the results demonstrate its effectiveness in accurately detecting islanding events. This approach provides a reliable and efficient solution for islanding detection in integrated distribution systems (IDS), playing a crucial role in ensuring the stability and reliability of power systems. The modeling and simulation are conducted using MATLAB software.